Synthesis and anti-tubercular activity of 3-substituted benzo[b]thiophene-1,1-dioxides - Chandrasekera, N. Susantha (PeerJ Inc., 2014)
We demonstrated that the 3-substituted benzothiophene-1,1-dioxide class of compounds are effective inhibitors of Mycobacterium tuberculosis growth under aerobic conditions. We examined substitution at the C-3 position of the benzothiophene-1,1-dioxide series systematically to delineate structure–activity relationships influencing potency and cytotoxicity. Compounds were tested for inhibitory activity against virulent M. tuberculosis and eukaryotic cells. The tetrazole substituent was most potent, with a minimum inhibitory concentration (MIC) of 2.6 µM. However, cytotoxicity was noted with even more potency (Vero cell TC50 = 0.1 µM). Oxadiazoles had good anti-tubercular activity (MICs of 3–8 µM), but imidazoles, thiadiazoles and thiazoles had little activity. Cytotoxicity did not track with anti-tubercular activity, suggesting different targets or mode of action between bacterial and eukaryotic cells. However, we were unable to derive analogs without cytotoxicity; all compounds synthesized were cytotoxic (TC50 of 0.1–5 µM). We conclude that cytotoxicity is a liability in this series precluding it from further development. However, the series has potent anti-tubercular activity and future efforts towards identifying the mode of action could result in the identification of novel drug targets.